2012
DOI: 10.1021/am3002499
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Healing Mechanisms of Carbon Fibers during the Catalytic Growth of Carbon Nanotubes on Their Surfaces

Abstract: This study reports on the main cause of the reduced tensile strength of carbon fibers (CFs) by investigating the microstructural changes in the CFs that are undergoing mainly two processes: catalyst nanoparticle formation and chemical vapor deposition (CVD). Interestingly, the two processes oppositely influenced the tensile strength of the CFs: the former negatively and the latter positively. The catalysts coating and nanoparticle formation degraded the CF surface by inducing amorphous carbons and severing gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…It was shown that the direct growth of CNTs onto carbon fiber surfaces can improve interfacial stresstransfer through the formation of a stiffer nanocomposite interphase around the fiber [6]. The CVD approach to integrating CNTs into fiber composites through direct-synthesis onto the fiber surface has been studied on a variety of substrates [6][7][8][9]. Subsequently, there have been numerous studies of the influence of CNT reinforcement on the mechanical and physical…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the direct growth of CNTs onto carbon fiber surfaces can improve interfacial stresstransfer through the formation of a stiffer nanocomposite interphase around the fiber [6]. The CVD approach to integrating CNTs into fiber composites through direct-synthesis onto the fiber surface has been studied on a variety of substrates [6][7][8][9]. Subsequently, there have been numerous studies of the influence of CNT reinforcement on the mechanical and physical…”
Section: Introductionmentioning
confidence: 99%
“…properties of these composites [7,[10][11][12][13][14][15]. The high temperatures combined with the reactive conditions in the CVD chamber can result in degradation of the properties of the fiber due to surface defects introduced by the catalyst [16].…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to the above results, Naito et al [16] and Kim et al [17] reported that the strength of carbon fibers increased by more than 10% during CVD process. Kim et al [17] found that the repair to some of the damage incurred during the catalytic deposition, an increase of carbon crystal size, and the formation of crosslinks of neighboring crystal all occur during CVD process, and contribute the improvement. In this study, such healing mechanism did not occur, therefore the strength of grafted fiber decreased by the pits generated by catalytic deposition.…”
Section: Single Fiber Tensile Testsmentioning
confidence: 59%
“…The introduction of CNTs into conventional fibre reinforced polymer composites creates a hierarchical reinforcement structure and can improve composites performance [7][8][9][10][11][12][13][14][15][16][17]. The addition of CNTs into conventional composites modifies the IFSS of composites; therefore it can improve the strength of them.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Retaining the mechanical properties of the pristine carbon fiber after batch CVD CNT-grafting has been reported by various means, including, reducing the temperature during CVD CNT-synthesis (ca. 500 °C), [22] as well as prolonged [23] or minimal [24,25] exposure to the CVD conditions. Optimized CNT-synthesis reaction gas stoichiometry [26] or tensioning fibers during CNT synthesis to reduce thermally-activated mechanochemical changes of the fiber microstructure [27] were also shown to limit damage of the carbon fiber substrate during CNT-synthesis.…”
Section: Introductionmentioning
confidence: 99%